2023
DOI: 10.1186/s12905-023-02262-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations with physical activity, sedentary behavior, and premenstrual syndrome among Chinese female college students

Abstract: Purpose Premenstrual syndrome refers to a set of distressing symptoms experienced before the menstrual flow, which can affect female students’ behavior, cognitive abilities, mental health status, and academic performance. Identifying modifiable risk factors is essential to reduce the prevalence college students’ premenstrual syndrome. We examined associations between premenstrual syndrome and physical activity and sedentary behavior in Chinese female college students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…Based on title and abstract screening, 123 records were excluded. By further full-text screening, 5 eligible publications [ 12 , 17 , 18 , 24 , 25 ] were included in the meta-analysis. The literature search process and results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on title and abstract screening, 123 records were excluded. By further full-text screening, 5 eligible publications [ 12 , 17 , 18 , 24 , 25 ] were included in the meta-analysis. The literature search process and results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies investigating the association between physical activity and premenstrual syndrome among female college students have reported inconsistent findings. For instance, moderate or high physical activity is associated with milder symptoms of premenstrual syndrome [ 12 , 17 , 18 ]. However, Sahin et al suggested that physical activity was not sufficient to yield beneficial effects on premenstrual syndrome [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Third, although our study has adjusted for several known confounders, there remains the potential for residual confounding due to uncollected factors ( e.g. , physical activities) 68,69 and possible misclassification of confounders, such as the use of self-reported weight and height for BMI calculation. 70 Fourth, the participation rate was fairly good in the School of Medicine, while the lower rate in other schools is due to the ongoing data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Para a coleta das informações, o formulário virtual foi divido em seções e abrangeu informações sobre aspectos sociodemográficos, hábitos culturais e antecedentes ginecológicos. Além disso, avaliou-se o diagnóstico, os principais sintomas e o impacto da SPM no desempenho acadêmico por meio da escala internacional The Premenstrual Syndrome Screening Tool (PSST), a partir de sua versão validada para o Brasil (Câmara et al, 2016;Śliwerski, Koszałkowska, 2021;Shi et al, 2023).…”
Section: Métodosunclassified